English Learning System in Islamic Boarding School: A Comparative Study - Akbarani, Rizqi; Pamungkas, Firdaus Ditya; Fahmi, Ahmad Lukman (JETLEE : Journal of English Language Teaching, Linguistics, and Literature, 2026)
In this era, the use of English is really needed in all aspects of education, even in Islamic boarding schools. Implementing English language learning in Islamic boarding school is a challenge, where students who focus on learning about Islamic studies are also demanded to learn and practice English skills. Therefore, the use of suitable and effective English learning system will decide to outcome of English learning in Islamic boarding schools. This study wants to compare English learning systems used by two Islamic boarding schools, in level of Junior High School. The comparation includes kinds of English learning activities, media for learning English, and obstacles of teachers during English learning activities. This study will use qualitative research where the data will be taken from and interview of English teachers of two Islamic Boarding Schools. The result show that there are some differences in kinds of English learning activities. However, the two Islamic boarding schools mostly have similarity in media for English learning and obstacles of teachers during English learning activities. Building students’ confidence is not only felt by English teachers during English learning, but mostly teachers also feel the same obstacle for their students.